Approaches to Improve Chemically Defined Synthetic Peptide Vaccines - Hos, Brett J.; Tondini, Elena; van Kasteren, Sander I.; Ossendorp, Ferry (Frontiers in Immunology, 2018)
Progress made in peptide-based vaccinations to induce T cell dependent immune responses against cancer has invigorated the search for optimal vaccine modalities. Design of new vaccine strategies intrinsically depends on the knowledge of antigen handling and optimal epitope presentation in both MHC class I and -II molecules by professional antigen presenting cells to induce robust CD8 and CD4 T cell responses. Although there is a steady increase in the understanding of the underlying mechanisms that bridges innate and adaptive immunology, many questions remain to be answered. Moreover, we are in the early stage of exploiting this knowledge to clinical advantage. Several adaptations of peptide-based vaccines like peptide-adjuvant conjugates have been explored and showed beneficial outcomes in preclinical models; but in the clinical trials conducted so far, mixed results were obtained. A major limiting factor to unravel antigen handling mechanistically is the lack of tools to efficiently track peptide vaccines at the molecular and (sub)cellular level. In this mini-review, we will discuss options to develop molecular tools for improving, as well as studying, peptide-based vaccines.